2023
DOI: 10.1007/s13577-023-00884-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and functional roles of EIF4G1 in lung squamous cell carcinoma

Abstract: Eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) is highly expressed in many cancers and affects their occurrence and development. However, the effect of EIF4G1 on the prognosis, biological function and the relevant mechanism in lung squamous cell carcinoma (LSCC) is unclear. Through clinical cases, Cox’s proportional hazard model and Kaplan–Meier plotter survival analysis, we find the expression levels of EIF4G1 are dependent on age and clinical stage, high expression of EIF4G1 could be used to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The translation initiation factor, EIF4G1, is highly expressed in a variety of tumors, and its ability to regulate the expression of numerous proteins has an important impact on tumor proliferation, migration, secretion of cytokines, and tumor angiogenesis (Fan et al, 2010;Hsieh et al, 2012;Robichaud et al, 2015). Previously, our group found that EIF4G1 expression is significantly higher in NSCLC tissues than in paraneoplastic tissues and affects patient prognosis, such that high expression of EIF4G1 in tumor tissues predicts shorter patient survival (Bai et al, 2023). The present study further explored the functions of EIF4G1 in tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The translation initiation factor, EIF4G1, is highly expressed in a variety of tumors, and its ability to regulate the expression of numerous proteins has an important impact on tumor proliferation, migration, secretion of cytokines, and tumor angiogenesis (Fan et al, 2010;Hsieh et al, 2012;Robichaud et al, 2015). Previously, our group found that EIF4G1 expression is significantly higher in NSCLC tissues than in paraneoplastic tissues and affects patient prognosis, such that high expression of EIF4G1 in tumor tissues predicts shorter patient survival (Bai et al, 2023). The present study further explored the functions of EIF4G1 in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous research, we found that the expression of EIF4G1 changes during tumor development. Future studies will investigate whether chemotactic macrophages entering the TME are affected by varying levels of EIF4G1 expression (Bai et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…EGF is an epidermal growth factor and is associated with cell proliferation in several types of cancer. EIF4G1 is associated with tumor microenvironment regulation and metastasis in breast cancer [72], and other studies report it as a possible prognostic indicator in squamous cell lung carcinoma [73]. FOXG1 is associated with the proliferation and invasion of renal clear cell carcinoma, as well as improved accuracy in prognosis prediction models [74].…”
Section: Cluster Molecular Profile and Lusc Genetic Signaturesmentioning
confidence: 96%